Angiomyolipoma of the nasal cavity - Dawlatly, E.E.; Anim, J.T.; El-Hassan, A.Y. (Journal of Laryngology and Otology, 1988)
Vascular tumours of the nasal cavity are uncommon and are either hamartomas or true neoplasms, mostly benign. We present an unusual case of angiomyolipoma of the nasal cavity. This harmartomatous lesion is often described in the kidney and may be associated with tuberous sclerosis. To our knowledge, there is no previous report of the lesion in the nasal cavity, and no association with tuberous sclerosis has been demonstrated in this case.
Keywords: Case Report; Hemangioma; Human; Lipoma; Male; Middle Age; Nasal Cavity; Nose Neoplasms